Review of research progress on soil moisture sensor technology - Yu, Limin; Gao, Wanlin; Shamshiri, Redmond R.; Tao, Sha; Ren, Yanzhao; Zhang, Yanjun; Su, Guilian (International Journal of Agricultural and Biological Engineering, 2021)
Soil moisture is directly related to the amount of irrigation in agriculture and influences the yield of crops. Accordingly, a soil moisture sensor is an important tool for measuring soil moisture content. In this study, the previous research conducted in recent 2-3 decades on soil moisture sensors was reviewed and the principles of commonly used soil moisture sensor and their various applications were summarized. Furthermore, the advantages, disadvantages, and influencing factors of various measurement methods employed were compared and analyzed. The improvements were presented by several scholars have established the major applications and performance levels of soil moisture sensors, thereby setting the course for future development. These studies indicated that soil moisture sensors in the future should be developed to achieve high-precision, low-cost, non-destructive, automated, and highly integrated systems. Also, it was indicated that future studies should involve the development of specialized sensors for different applications and scenarios. This review research aimed to provide a certain reference for application departments and scientific researchers in the process of selecting soil moisture sensor products and measuring soil moisture. Keywords: soil moisture sensor, measurement principle, influencing factor, improvement method, development direction DOI: 10.25165/j.ijabe.20211404.6404 Citation: Yu L M, Gao W L, Shamshiri R R, Tao S, Ren Y Z, Zhang Y J, et al. Review of research progress on soil moisture sensor technology. Int J Agric & Biol Eng, 2021; 14(4): 32–42.